Biopolymers for seed presowing treatment - Struminska, Olena; Kurta, Sergey; Shevchuk, Liliya; Ivanyshyn, Stanislaw (Publishing House of Lviv Polytechnic National University, 2014)
Physico-chemical properties of specially modified forms of natural biopolymers – carboxymethyl cellulose and xanthan gum – were studied. The effectiveness and ability to film formation of water soluble polymeric compositions of these biopolymers, their influence on the growth and productivity of agricultural crops were examined. The effect of the biopolymers, mineral fertilizers and micronutrients content in the solution on its viscosity, as well as the dependence of the formed films thickness on the content of modified biopolymers and fertilizers were investigated. It was established that using natural film-forming compositions the consumption of fertilizers and micronutrients per hectare of crops reduces significantly (by 10–100 times), the yield of plants increases by 15–80 %. The compositions are characterized by high sanitary, hygienic and ecological indicators. Розглянуто фізико-хімічні властивості спеціально модифікованих форм природних біополімерів – карбоксиметилцелюлози та ксантанової смоли. Проведено дослідження ефективності та здатності до плівкоутворення водорозчинних композицій цих біополімерів, їх впливу на ріст і продуктивність сільськогосподарських культур. Досліджено залежності між зміною вмісту біополімерів, мінеральних добрив і мікроелементів у розчині та його в׳язкістю, а також залежність товщини утворених плівок від вмісту модифікованих біополімерів та мінеральних добрив. Встановлено, що застосовування природних плівкоутворюючих композицій значно, у 10–100 раз, знижує розхід мінеральних добрив та мікроелементів на гектар посівів та підвищує на 15–80% врожайність сільськогосподарських культур. Композиції характеризуються високими санітарно-гігієнічними та екологічними показниками.
Біополімери для передпосівного оброблення насіння
Keywords: biopolymer; carboxymethyl cellulose; xanthan gum; mineral fertilizers; ultrasound; modifier біополімер; карбоксиметилцелюлоза; ксантанова смола; мінеральні добрива; ультразвук; модифікатор